PENGEMBANGAN MEDIA FIPBOOK DIGITAL PADA MATERI INDONESIAKU KAYA RAYA KELAS V SD - Lia Rohayani; Marhamah; Puji Ayurachmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This researcher aims to produce a digital flipbook media on the Material Indonesiaku Kaya Raya which is valid and practical for fifth grad students of SD Negeri 90 Palembang. The type of research used is R&D and uses the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. The data collction teacniques used are observation, questionnaires and documentation. Based on the result of the research of the digital flipbook media validator expert that wa developed, it obtained a validity level of 85,8% categorized as “Very Valid”. Then the practicality test of the teacher questionnaire response obtained a result of 93,3% categorized as “Very Practical”, the one to one student questionnaire response obtained a result of 90% categorized as “Very Practical”, the small group student v questionnaire response obtained a result of 91% categorized as “Very Practical”,and the large group student questionnaire response obtained a result of 90,1% categorized as “Very Practical”.